Influence of Price and Product Quality Analysis on Frozen Fish Purchasing Decisions - Endrawati, Titin; Karundeng, Deby R.; Cakranegara, Pandu Adi; Putri, Raudya Setya Wismoko; Nofirman, Nofirman (Agrikan: Jurnal Agribisnis Perikanan, 2022)
The purpose of this study was to analyze the effect of price and product quality on the decision to purchase frozen fish products at a store that sells a variety of frozen food products. The research design used in this study uses a quantitative associative method. Based on the results of data analysis that has been carried out in the first hypothesis (H1), which states that price has a positive and significant effect on purchasing decisions, the t-count value of 15,127 is greater than the t-table value, which is 1,667, testing the second hypothesis (H2). Which states that the quality of the product has a positive and significant effect on purchasing decisions the t-count value is 24,325 greater than the t-table value, which is 1,667, which means that the price and product quality produced have a positive and significant effect on consumer purchasing decisions. While the R-square value obtained is 0.781 which states that the price and product quality variables influence consumer purchasing decisions by 78.10% and the remaining 21.90% are influenced by other variables.